Femtosecond laser inscribed phase masks for fibre Bragg grating sensor inscription - Sugden, Kate; Lee, Graham; Kalli, Kyriacos; Yan, Zhijun; Adebayo, Dotun; Komodromos, Michael; Koutsides, Charalambos (My University, 2012)
We present femtosecond laser inscribed phase masks for the inscription of Bragg gratings in optical fibres. The principal advantage is the flexibility afforded by the femtosecond laser inscription, where sub-surface structures define the phase mask period and mask properties. The masks are used to produce fibre Bragg gratings having different orders according to the phase mask period. The work demonstrates the incredible flexibility of femtosecond lasers for the rapid prototyping of complex and reproducible mask structures. We also consider three-beam interference effects, a consequence of the zeroth-order component present in addition to higher-order diffraction components. 2012 SPIE.
Keywords: Femtosecond laser inscriptions; Fibre bragg grating sensors; Higher-order diffraction; Inscription; Interference effects; Laser-material interactions; Phase masks; Talbot effects; Fiber bragg gratings; Masks; Rapid prototyping; Ultrafast lasers; Ultrashort pulses